K-Means And K-Medoids Algorithms For Food Clusterization Optimized By Nutritional Value - Eko Nugroho, Wildani; Dwi Kurniawan, Safar; Alga Vredison, Prayoga; Firmansyah, Hasbi (Publisher Cv. Inara, 2025)
This study examines the impact of flexible work arrangements on productivity in start-up companies located in Bandung Techno Park, using work-life balance as a mediating variable. With a sample size of 168 start-up company members in Bandung Techno Park (BTP), this study uses a probability sampling technique. This study uses quantitative research techniques and structural equal modeling (SEM) based on partial least squares (PLS-SEM) for data analysis. Based on the results of the study, work-life balance and increased productivity are greatly enhanced by flexible work arrangements. The mediating variable of work-life balance acts as a mediator between productivity and flexible work schedules. The findings of this study can be a guide for business management who want to increase the productivity of start-up companies through work arrangement solutions that support work-life balance.